Diagnostic Accuracy of Lead aVR (in surface ECG) for Confirming Atrio Ventricular Nodal Reentry Tachycardia - Hamid*, MD Abdul; Hussain, Mohsin; zaman, Asif; Siddike, Sohel; Mamun, Al; Islam, A F M Rezaul; Sonali, Tahmina Alam; Houqe, Faridul; Das, Rajat Shuvra (Cardiology and Cardiovascular Medicine, 2024)
Introduction: Slow-fast atrioventricular node re-entrant (AVNRT) the common forms of supraventricular tachycardia (SVT). Electrocardiogram (ECG) during tachycardia helps distinguish between them, often using pseudo R' wave in lead V1 and pseudo-S wave in inferior leads, but the value of an isolated aVR lead remains unexplored. Aim of the study: The aim of this study was to find out the diagnostic accuracy of the aVR lead of the surface ECG for AVNRT. Methods: This cross-sectional observational study was conducted at the department of Cardiology and Electrophysiology, National Institute of Cardiovascular Diseases & Hospital, for 1-year period. After obtaining consent and ensuring ethical compliance, patients underwent electrophysiological study and radiofrequency ablation, to estimate sensitivity, specificity, and positive predictive values for AVNRT. Result: Among the 62-study population, 41 had AVNRT and 21 had AVRT. The mean age of AVNRT patients was 41.3±9.7 years ranging from 13 to 65 years. About 63.4% were female and 36.6% were male. Among patients who had AVNRT, 61% had pseudo r′ wave in aVR. The overall sensitivity and specificity of lead aVR in the AVNRT was 61% and 85.7%; respectively which is 53.7% and 81% for pseudo-R’-wave in V1, 61% and 76.2%; for pseudo-S-wave, 41.5% and 90.5%; for classical AVNRT criteria. Conclusion: The detection of a pseudo–R in aVR lead could be as useful criteria for the diagnosis.